Clinicopathological Correlation in Patients of Lymphadenopathy in Tertiary Care Hospital - Rajhans, MD, Dr. Amol R.; Howale, Dr. Deepak S. (International Journal of Innovative Research in Medical Science, 2018)
Lymph nodes are parts of the lymphatic system. Lymph node helps to filter out viruses, bacteria, cancer cells and other unwanted substances safely removed from the body. Lymphadenopathy is common clinical problem frequently give dilemma in diagnostic. Enlargement of lymph node is a common problem which evaluate as a Lymphadenopathy. An abnormality in size and character of lymph node in known as Lymphadenopathy which also consider as enlarged abnormally that measures more than 10mm in its diameter than normal. Lymphadenopathy is common clinical problem frequently give dilemma in diagnostic. Fine needle aspiration cytology (FNAC) has become an important tool for initial diagnosis and management for patients suffering from Lymphadenopathy because of early result, simple for test and minimal trauma to patient. The main aim of this study is to Correlation of Clinicopathological condition presenting with Lymphadenopathy. Role of FNAC in diagnosis will also evaluate with node biopsy and open lymph. Material and methods: Total 100 patients were included in this study. For all 100 patients fine needle aspiration cytology (FNAC) was done. In 75 cases excision biopsy was done. Pathological diagnosis was obtained in all cases. Fine needle aspiration cytology, excision biopsy, throat, ear and nose examination were carried out as a required base line investigations. Result: Total 80 patients were studies in this study. Out of this 80 patients 30 cases were IPD and remaining were OPD. FNAC as well as biopsy were carried out from total patients in this study. In this study Tubercular Lymphadenitis was observer maximum. Out of 80 patients 47(58.75%) were male and 33(41.25%) were female patients. Age group 20-30 years (35%) were maximum number of patients which was followed by 30-40 years (23.75%) and 10-20 years (21.25%) respectively was observed. Out of 80 patients 50(62.5%) were diagnosis as Tubercular Lymphadenitis and Chronic Non-specific Lymphadenitis was diagnosis in 10 (12.5%). Reactive lymphadenitis was diagnosed in 8(10%) patients whereas Malignant secondary’s were diagnosed in 7(8.75%) patients followed by 3(3.75%) patients suffer from lymphomas and 2(2.5%) were Non- Hodgkin's Lymphoma. Conclusion: Lymphadenopathy is a clinical evaluation followed by FNAC which is reliable diagnostic tool that is easy to perform; cost effective, speedy results accurate can be obtained. Specialist input is the main requirement for this. Biopsy is also useful in cases of lymphomas that act as diagnostic tool. When FNAC report is inconclusive, in nonspecific lymphadenitis than Biopsy is much helpful for accurate diagnosis and management. Hence, in cases of Lymphadenopathy FNAC was found to be reliable, simple and cost effective method for diagnosis.